Osgood-schlatter disease in adult: would early diagnosis and treatment improve the prognosis?/ Nurul Hidayatullaila Sahar ... [et al.] - Sahar, Nurul Hidayatullaila; Ramli, Anis Safura; Badlishah-Sham, Siti Fatimah; Mohd Miswan, Mohd Fairudz (Faculty of Medicine, 2023)
Osgood-Schlatter Disease (OSD) is a juvenile osteochondritis of tibial tuberosity affecting athletic adolescents. However, the classical feature of persistent para-patellar pain is uncommon in skeletally mature adults. This case presents a 23-year-old gentleman with an 8year history of bilateral anterior knee pain and swelling. The symptoms began after a sports injury which occurred when he was 15. The diagnosis of OSD was missed at this point as the presentation and radiological features mimic cracked fracture of the tibial tuberosity. Subsequently, he did not obtain medical care which resulted in worsening knee pain and swelling. Recent X-ray showed fragmented apophysis in both knees, supporting the diagnosis of bilateral OSD. Further evaluation suggests that he probably developed OSD long before he presented with the sport injury. This case highlights the importance of early diagnosis and management of OSD in childhood to improve the prognosis and reduce the risk of complications in adulthood.